Digital Communication Management Bandung City Government in Inclusive and Sustainable Economic Recovery in Bandung City - Retno Ekasari; Saktisyahputra Saktisyahputra; Nur Ambulani; Syubhan Akib (Yayasan Ilomata, 2023)
The COVID-19 pandemic has occurred in the world since 2020, not only in Indonesia but also in all countries in the world. The economic impact of the Covid-19 pandemic has been felt by the Indonesian people since the implementation of the Large-Scale Social Restrictions (PSBB) on March 15, 2020. Community activities are forced to be carried out through digital transformation in services, transactions and work, for example the Bandung City Government. This research was conducted to determine the Digital Communication Management of the Bandung City Government in an inclusive and sustainable Economic Recovery in Bandung City. The object of this research is the Bekasi City Government. This study uses the method of Phenomenology of Edmund Husserl. Having the concept of phenomenology as a scientific method that does not start with doubt, direction, and the truth of an experience. Data collection techniques in this study by means of observation, interviews, and documentation. Data analysis techniques in this study use data reduction, data display, and verification of Miles and Huberman. Based on the Data Findings, Data Results and Discussions that the researchers have submitted, it can be concluded that the Bandung City Government has implemented Digital Communication Management in helping inclusive and sustainable economic recovery by through digital platforms, it is more helpful for small entrepreneurs, especially the current focus on Micro, Small and Medium Enterprises. One of them is Digital Transformation by continuing to encourage the implementation of smart cities through digital transformation in various aspects of public services.